2012
DOI: 10.1128/aem.07242-11
|View full text |Cite
|
Sign up to set email alerts
|

Germinant-Enhanced Decontamination of Bacillus Spores Adhered to Iron and Cement-Mortar Drinking Water Infrastructures

Abstract: ABSTRACTGermination was evaluated as an enhancement to decontamination methods for removingBacillusspores from drinking water infrastructure. Germinating spores before chlorinating cement mortar or flushing corroded iron was more effective than chlorinating or flushing alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Both experiments include injection of BG spores into an experimental pipe system, allowing them to come into Chlorine dioxide concentration-mg/L contact with cement-mortar drinking water infrastructure surfaces, followed by chlorine dioxide decontamination; however, the pilot-scale system is made of PVC with iron and cement-mortar coupons inserted that allow for biofilm growth. A detailed description of the pilot scale system at the T&E facility can be found in Szabo et al 2012. After injection of BG spores into the WSTB facility-pipe bulk-water phase, spores were detected at approximately 10 6 cfu/mL.…”
Section: Experimental Decontamination Results and Discussionmentioning
confidence: 99%
“…Both experiments include injection of BG spores into an experimental pipe system, allowing them to come into Chlorine dioxide concentration-mg/L contact with cement-mortar drinking water infrastructure surfaces, followed by chlorine dioxide decontamination; however, the pilot-scale system is made of PVC with iron and cement-mortar coupons inserted that allow for biofilm growth. A detailed description of the pilot scale system at the T&E facility can be found in Szabo et al 2012. After injection of BG spores into the WSTB facility-pipe bulk-water phase, spores were detected at approximately 10 6 cfu/mL.…”
Section: Experimental Decontamination Results and Discussionmentioning
confidence: 99%
“…A bioterrorist attack in food could potentially create huge financial cost to the impacted industry regarding the cleanup. The resistance of B. anthracis spores to disinfec tants and other inactivation methods were reported by some researchers (9,11,13). Another study showed that some disinfectants have a great effect in inactivating B. anthracis spores in the presence of food residues (3).…”
mentioning
confidence: 89%
“…Addition of a germinant (50% Trypticase™ soy broth) into a model distribution system, followed by flushing, was found to enhance the efficacy of chlorine (5 mg L −1 ) and encourage detachment of BG spores from established biofilms on concrete and iron surfaces, resulting in no detectable spores (>4 log 10 CFU cm −2 reduction) (Szabo et al 2012). Morrow & Cole (2009) also demonstrated enhanced chlorine efficacy after addition of germinant (1 mM inosine and 8 mM l-alanine) to a biofilm reactor containing B. anthracis Sterne spores associated with an established biofilm.…”
Section: Biofilms and Amoebamentioning
confidence: 99%